2021
DOI: 10.3390/nu13113931
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Improve Gastrointestinal Function and Life Quality in Pregnancy

Abstract: We studied whether probiotics were beneficial for hormonal change-associated dysbiosis, which may influence the enteric nervous system and GI function during early pregnancy. The study was 16 days consisting of two cycles of six daily probiotics mainly Lactobacillus and 2 days without probiotics. Daily surveys were conducted to monitor GI function and life quality. A subset of the participants who contributed fecal specimens was used for microbiota metagenomic sequencing, metabolomics, and quantification of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…This could be explained in the light of, the probiotic intake increased the level of Bile Salt Hydrolase generating bacteria, which produced free bile acids that enhancing gastrointestinal motility and metabolism and it also have the antiinflammatory and metabolic effects (Săsăran, 2023;Bourgin et al,2021). Liu et al, (2021) who studied the effect of probiotics on improvement of gastrointestinal function also support the results of the present study were mentioned that probiotic intake significantly reduced frequency of vomiting. The findings that have been shown by Yossef et al, (2019) were also congruent with these results were stated that probiotics produced highly statistically significant improvement in gastrointestinal symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…This could be explained in the light of, the probiotic intake increased the level of Bile Salt Hydrolase generating bacteria, which produced free bile acids that enhancing gastrointestinal motility and metabolism and it also have the antiinflammatory and metabolic effects (Săsăran, 2023;Bourgin et al,2021). Liu et al, (2021) who studied the effect of probiotics on improvement of gastrointestinal function also support the results of the present study were mentioned that probiotic intake significantly reduced frequency of vomiting. The findings that have been shown by Yossef et al, (2019) were also congruent with these results were stated that probiotics produced highly statistically significant improvement in gastrointestinal symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Administration of probiotic enteric-coated capsules in combination with ursodeoxycholic acid soft capsules to 82 ICP patients increased alkaline phosphatase (ALP) and γ-glutamyltransferase (γ-GT) enzyme levels and decreased blood ammonia (BA) levels. These effectively improved the liver function and intestinal flora of ICP patients [90]. Another probiotic, L. rhamnosus LRX01, was found to inhibit the expression of FXR in the ileum of pregnant ICP patients.…”
Section: Biomedicines (Probiotics) In Hepatobiliary Disease During Pr...mentioning
confidence: 96%
“…94 One study conducted in pregnant women showed that probiotic could increase the copy numbers of bsh, which were notably correlated with lower vomiting scores and times. 95 TCA is a powerful trigger for Clostridioides difficile infection, while BSH can hydrolyse TCA to cholic acid, which can inhibit the growth of C. difficile. 96 Some BAs are toxic due to their acidic properties and detergent-like properties, BSH enzyme can promote deconjugation of conjugated BAs and eliminate their inherent detergent properties.…”
Section: Bsh Modulates the Balance Of The Gut Microbiota And Host Healthmentioning
confidence: 99%
“…94 One study conducted in pregnant women showed that probiotic could increase the copy numbers of bsh , which were notably correlated with lower vomiting scores and times. 95 TCA is a powerful trigger for Clostridioides difficile infection, while BSH can hydrolyse TCA to cholic acid, which can inhibit the growth of C. difficile. 96…”
Section: The Bsh-harboring Gut Microbes Play An Essential Role In Mai...mentioning
confidence: 99%